Risk Factors Analysis in Recurrent Stroke Events: Literature Review - Sayeeda, Adinda; Agianto, Agianto; Agustina, Rismia; Rizany, Ichsan (Berkala Kedokteran, 2023)
After the first stroke, according to epidemiological data, there is a 30% risk of recurrent stroke. That events are the population who had suffered stroke and the recurrence rate is 9 times compared to the normal population. Results of research from the Stroke Association stated that the possibility of recurrence stroke was 3.1% in 30 days, 11.1% within one year, 26.4% within five years, and 39.2% within 10 years. This literature review is intended to analyze the risk factors of recurrent stroke events. The literature review was carried out by searching for articles in 2011-2021 in Indonesian and English. There were four databases for providing electronic journal articles, namely Garuda, Google Scholar, Science Direct, and PubMed. The quality of the articles carried out using JBI's Critical Appraisal Tools. Narrative synthesized was used to analyze the data of the review.  There were 6 articles synthesized in this review. The review result showed that diabetes mellitus, hypertension, cardiovascular disorders, anemia, obesity, lack of physical activity, high serum of LDL/HDL, non-adherence to treatment, lack of confidence in treatment, lack of knowledge about the disease, and gender can encourage the occurrence of recurrent stroke. Many factors cause recurrent stroke events but diabetes mellitus, hypertension and  non-adherence to treatment are most widely discussed in the six articles.